Analisis Manajemen Risiko Operasional Berdasarkan Pendekatan Enterprise Risk Management (ERM) pada Pink Chilling Cabang Pancing - Caroline Margaretha Silitonga; Riama Pakpahan; Ronaldi Simanjuntak (MISTER: Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This research aims to analyze operational risk management at Pink Chilling Pancing branch using the Enterprise Risk Management (ERM) approach. The background to this research is based on the importance of company awareness of operational risks that can affect business continuity. The operational risks identified include technology, human resources, environmental and process risks. Through qualitative methods based on literacy studies and interviews with outlet owners, this research identifies the risks faced by the company and evaluates the severity and likelihood of these risks occurring. The analysis results show that the highest risk is the risk of the ice machine shutting down due to a power outage. Risk assessment is carried out using frequency and impact tables, which are then categorized into three levels: low, medium and high. Risk control is focused on medium and high level risks, with strategies such as providing alternative electricity sources and other preventive measures. This research concludes that implementing ERM can help Pink Chilling identify, assess and manage risks effectively. Recommendations are provided to implement ERM comprehensively and expand the research focus to other risk aspects such as financial, strategic and market risks for a more holistic view of risk management.